2017
DOI: 10.1007/s12665-017-6445-8
|View full text |Cite
|
Sign up to set email alerts
|

A study of gross alpha and beta measurements for thermal springs in Central Anatolia, Turkey

Abstract: A screening of natural radioactivity content has been carried out in thermal water samples collected from surrounding of Central Anatolia, Turkey. The concentration levels of gross alpha and beta of 19 different samples has been determined using the low background gas-flow proportional counter. The measured gross alpha and beta activities in waters range from 0.11 to 16 Bq/L and 0.10 to 16.9 Bq/L, respectively. The measured values of gross alpha and beta concentrations are compared to previous studies in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…(Fasae, 2013 andOluwole et al 2020). For reported studies outside Nigeria (Natural spring, Tap and River, Thermal spring, River and Borehole/Well) the activity concentration of gross alpha and beta are lower than reports of Kobya et al (2015), Korkmaz et al (2016), Sahin et al (2017), Selcuk et al (2009) and Darko et al (2014) respectively as shown in Table 2. The lower activity concentrations of gross alpha and beta in this study compared to other studies is due to the geological properties of the source of water and the activities carried out around the water source.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…(Fasae, 2013 andOluwole et al 2020). For reported studies outside Nigeria (Natural spring, Tap and River, Thermal spring, River and Borehole/Well) the activity concentration of gross alpha and beta are lower than reports of Kobya et al (2015), Korkmaz et al (2016), Sahin et al (2017), Selcuk et al (2009) and Darko et al (2014) respectively as shown in Table 2. The lower activity concentrations of gross alpha and beta in this study compared to other studies is due to the geological properties of the source of water and the activities carried out around the water source.…”
Section: Resultsmentioning
confidence: 70%
“…The gross alpha and beta counting is a relatively simple, stable, and low cost preliminary test, as stipulated in the guidelines set by WHO for water quality determination (WHO, 2004). It has also become a veritable tool for determination of relative radioactivity levels in water (Jobbagy et al, 2011;Sahin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(2016) 0.012 0.234 Tap water Saleh et al. (2015) 0.11–16 0.10–16.90 Thermal spring water Sahin et al. (2017) 0.0157–0.1427 0.0893–0.400 Borehole and well water Darko et al.…”
Section: Resultsmentioning
confidence: 99%
“…The gross alpha and beta counting is the preliminary test, as stipulated in the World Health Organization guideline for water quality determination ( WHO, 2004 ). Also, due to its relatively stability, low costs and simplicity, it has become a veritable tool for determination of relative radioactivity levels in water ( Jobbágy et al., 2011 ; Sahin et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%